2008
DOI: 10.1097/mot.0b013e3283071450
|View full text |Cite
|
Sign up to set email alerts
|

Defining unacceptable HLA antigens

Abstract: The definition of unacceptable antigens is determined by the clinical protocols and the physiological and immunological characteristics of the recipient and donor. These data should be integrated to maximize the opportunity for transplantation. The development of additional tests to assess a patient's capacity for recognizing and responding to a transplant will improve the identification of incompatible donor-recipient pairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 45 publications
0
30
0
2
Order By: Relevance
“…Some unacceptable HLA antigens are sufficiently rare that the CPRA value rounds to zero; however, kidneys from donors with those rare antigens are not offered to the patient. The CPRA is based on HLA-A,-B,-DR and -DQ frequencies derived from the phenotypes of 12 061 donors in the OPTN registry as previously described (8). The HLA-C antigens are currently excluded from the CPRA calculation because there was inadequate donor typing data to estimate their frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…Some unacceptable HLA antigens are sufficiently rare that the CPRA value rounds to zero; however, kidneys from donors with those rare antigens are not offered to the patient. The CPRA is based on HLA-A,-B,-DR and -DQ frequencies derived from the phenotypes of 12 061 donors in the OPTN registry as previously described (8). The HLA-C antigens are currently excluded from the CPRA calculation because there was inadequate donor typing data to estimate their frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…This correlation allowed prediction of the result of flow cytometry and CDC crossmatches in 92.8 and 92.4 % of cases. One of the major issues in virtual crossmatch using solid-phase assays is nonstandardized interpretation; therefore, antibody strength and titer, complement fixation, and sensitization events must be accurately considered [41,43,44]. Gandhi et al [45], in a retrospective study on heart transplantation, defined a virtual crossmatch as negative when MFI values, referring to antibodies identified by SA, were \300, and as positive for MFI values [1500.…”
Section: Virtual and Luminex Crossmatchmentioning
confidence: 99%
“…The ability of Luminex to identify anti-HLA antibodies has improved the definition of acceptable and unacceptable antigens, facilitating exchange of organs between different centers to facilitate transplantation in highly immunized patients [41]. Nevertheless, several studies have shown that low antibody levels are not always associated with adverse effects.…”
Section: Virtual and Luminex Crossmatchmentioning
confidence: 99%
“…Также необходимо выпол-нение и донору, и реципиенту HLA-типирования с высоким разрешением. Задачами иммунологиче-ского подбора донорского органа следует считать, во-первых, отсутствие у донора тех антигенов HLA, к которым у кандидата на трансплантацию есть ан-титела, и во-вторых, достижение максимальной совместимости по системе HLA [6]. Недостатком такого метода, особенно в группе высокосенсиби-лизированных пациентов, является значимое увели-чение сроков ожидания трансплантации.…”
Section: заключениеunclassified